Nilai-Nilai Rahmat Islam Dalam Konsep Hudud - Saputra, Adha; Erlina, Lira (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
This article highlights the values of Islamic mercy contained in the concept of Hudud. This article is needed as an answer to the criticism that the concept of hudud in Islam is against human rights (HAM). The type of research used is descriptive qualitative research using the library research method. This article finds that the mercy of Islam is very much reflected in the concept of hudud, starting from the proscription of hudud itself to its enforcement in the community, even when and after the enforcement of hudud, we are prohibited from denouncing, cursing, and berating the perpetrators of criminal acts, even Islam tells us to do good and pray for them. This shows that the concept of hudud in Islam contains values of mercy and is not against human rights.